STRATEGI PENANAMAN NILAI-NILAI ISLAM PADA KURIKULUM DAN BUDAYA SEKOLAH DI SD ISLAM AL-FURQON SUKAHAYU SUMEDANG - Khulasoh, Siti; Saefullah, Agus Susilo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Globalization has posed significant challenges to preserving Islamic values among younger generations. This study aims to identify strategies for instilling Islamic values through curriculum and school culture at SD Islam Al-Furqon Sukahayu Sumedang. A descriptive qualitative approach was employed, with data collected through document studies, in-depth interviews, and direct observation. Data were analyzed interactively through data reduction, presentation, and conclusion drawing, with validation carried out via source and method triangulation. The findings indicate that the school integrates Islamic values within the curriculum by dominating Islamic subjects, habituating Qur’an memorization (tahfidz), and scheduling that aligns with an Islamic lifestyle. As introduced by Philip W. Jackson, the hidden curriculum concept is evident in the cultivation of values through time management, teacher-student interaction, and a learning environment that nurtures Islamic character without direct instruction. Islamic values are also embedded in school culture, including congregational prayers, dhikr, Friday charity, and the early habituation of wearing modest clothing. Supporting factors include teacher development programs by the foundation, parental involvement in religious activities, and partnerships with institutions such as Baznas. Challenges include limited classroom space and suboptimal administrative communication systems between the school and parents. This study recommends improving physical facilities and developing a reporting system for religious activities to enhance the consistency and sustainability of Islamic values education.